Detecting human activity areas in Middle Palaeolithic open-air sites in Northern France from the distribution of faunal remains. (December 2021) - Moreau, Gwénaëlle; Auguste, Patrick; Locht, Jean-Luc; Patou-Mathis, Marylène
Highlights: Detecting human activity areas in Neanderthal sites using spatial analysis method. Built of an adapted methodology for our datasets and estimated its reproducibility. Study based on the combined use of Kernel Density Estimation and K-means clustering. Butchery and combustion areas were detected for both sites: Caours, Beauvais. We have refined the spatial criterion that may be recurrent in Neanderthal sites. Abstract: The detection of Middle Palaeolithic human activity areas represents a methodological challenge at the boundary between two disciplines: archaeology and spatial analysis. During the course of the past decades, with the democratisation of tools such as Geographic Information Systems (GIS), prehistorians have developed a wide diversity of methods for the study of the spatial organization of occupation levels. We must now choose the best adapted method to our spatial problems, our archaeological contexts, but also our set of geographic data, from the existing methods. In this context, we devised a new spatial analysis protocol, highlighting archaeological and spatial criteria that constrained our choice of methods and estimating their reproducibility. The construction and application of our protocol is based on the Middle Palaeolithic open-air sites of Caours and Beauvais, situated in the North of France. On account of the ideal preservation conditions at these sites, they are propitious candidates for spatial analysis. In addition, these sites rank among those with the most abundant faunal remains of the region and our study focuses on this category of remains. The combined use of two methods of spatial analysis – K-means clustering and Kernel Density Estimation – enables us, on one hand, to effectively detect human activity areas, their number and their distribution. On the other hand, this protocol contributed to their characterisation and the description of their role for the functioning of the occupation level. For both of the studied sites, we brought to light several areas of butchery activities organized around a combustion zone. In the case of Caours, areas of specific butchery activities, devoted to one or two species, were identified.